2011
DOI: 10.1017/s1355617711000403
|View full text |Cite
|
Sign up to set email alerts
|

Upper and Lower Extremity Motor Function and Cognitive Impairment in Multiple Sclerosis

Abstract: Motor impairments and cognitive dysfunction are common in multiple sclerosis (MS). We aimed to delineate the relationship between cognitive capacity and upper and lower motor function in 211 MS patients, and 120 healthy volunteers. Lower and upper motor function were assessed with the Timed 25 Foot Walk (T25FW) and the Nine Hole Peg Test (NHPT) as implemented in the Multiple Sclerosis Functional Composite (MSFC). Subjects also underwent neuropsychological evaluation. Hierarchical linear regression analysis was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
77
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1
1

Relationship

3
7

Authors

Journals

citations
Cited by 131 publications
(91 citation statements)
references
References 49 publications
9
77
2
Order By: Relevance
“…It has been shown that processing speed and executive function tests were significant predictors of lower and upper motor function in MS; where cognitive tests predicted variability in motor function after controlling for disease duration and physical disability. (20) We found a modest correlation between PASAT and T25FW, however, this effect was reduced to non-significant after controlling for age and EDSS.…”
Section: Discussioncontrasting
confidence: 54%
“…It has been shown that processing speed and executive function tests were significant predictors of lower and upper motor function in MS; where cognitive tests predicted variability in motor function after controlling for disease duration and physical disability. (20) We found a modest correlation between PASAT and T25FW, however, this effect was reduced to non-significant after controlling for age and EDSS.…”
Section: Discussioncontrasting
confidence: 54%
“…Given that there is evidence of coupling between cognitive and motor function in MS (Benedict et al, 2011) and in other clinical populations (Verghese et al, 2002) this was an unexpected observation. A potential explanation of this lack of association is that there may be distinct underlying mechanisms.…”
Section: Discussionmentioning
confidence: 91%
“…A dual task paradigm was also used to show that patients with MS had greater decrements in walking speed than healthy controls, and that the degree of the decrement was related to fatigue, measures of general cognitive function and self-reported cognitive errors rather than measures of overall disability [27]. Processing speed and EF were also found to be significant predictors of lower and upper motor function in patients with MS [28].…”
Section: Introductionmentioning
confidence: 99%